REMOTE WORK: TECHNOLOGIES AND EXPERIENCE OF THE ORGANIZATION - F. Konobevtsev; N. Laas; E. Gurova; I. Romanova (Вестник университета, 2019)
The types of remote employment (distance work and freelance) have been considered. Directions of use of modern information technologies at the organization of remote employment have been indicated and their developed characteristic has been given. The activity of freelancers has been described in detail. The mechanisms of functioning of international online labor exchanges and Russian platforms have been revealed. The results of a study on the practice of remote work in modern domestic organizations have been adduced. According to the results of the study, conclusions have been made about the areas of remote employment, its advantages and disadvantages for the organization and employees; about the software and hardware used by employers; about the problems of regulatory regulation of remote employment; about the competencies of remote workers and freelancers.